Stranski učinki kortikosteroidov za lokalno uporabo na koži in priporočila za varno uporabo - Benedičič-Pilih, Ana (Medicinski razgledi, 2001)
Topical corticosteroids for dermal use are among the most frequently used dermatologicals. Number of available agents of different strength and vehiclesis increasing. Along with recent development of high-potency topical corticosteroids, the potential for unpleasant adverse effects has increased. Therefore, clinicians should be familiar with the uses, adverse effects and contraindications of these preparations. The article presents principles of use of topical corticosteroids in the field of dermatology from the viewpoint of prevention of serious adverse effects, as adverse effects resulting from thoughtless and uncontrolled use of dermal steroids are often the reason for consultation with a dermatologist.
Keywords: Dermatitis alergijski, kontaktni; Skin diseases; Drug therapy; Hidrokortizon topični; Hydrocortisone, topical; Kožne bolezni; Therapeutic use; Dermatitis perioralni; Pigmentacija, motnje; Adverse effects; dermatologija; Dermatitis, allergic contact; Dermatitis, perioral; therapy; zdravljenje; zdravila; drug; Pigmentation disorders; kortikosteroidi; škodljive snovi